Adductor Lengthening and Rectus Abdominis Repair via a 2-Incision Approach for Treatment of Core Muscle Injuries: A Technique Guide - Alexander R. Rodriguez, M.D.; Nicholas J. Lanzetta, M.D.; Joshua T. Finerty, B.S.; Allison R. Garden, B.S.; Joshua S. Everhart, M.D., M.P.H. (Arthroscopy Techniques)
Core muscle injuries are a common source of groin pain in athletes. An understanding of the pathoanatomy and clinical workup for this condition will assist in correctly identifying core muscle injuries from other causes of groin pain. In cases refractory to nonoperative management, surgical intervention may be indicated. In this Technical Note, we describe a comprehensive approach for the clinical evaluation of core muscle injuries, indications for operative intervention, and a surgical technique for adductor lengthening and rectus abdominis repair via a 2-incision approach.